2‐Hydroxybenzophenone as a Chemical Auxiliary for the Activation of Ketiminoesters for Highly Enantioselective Addition to Nitroalkenes under Bifunctional Catalysis. (14th April 2018) - Guerrero‐Corella, Andrea; Esteban, Francisco; Iniesta, Manuel; Martín‐Somer, Ana; Parra, Mario; Díaz‐Tendero, Sergio; Fraile, Alberto; Alemán, Jose
Abstract: An organocatalytic system is presented for the Michael addition of monoactivated glycine ketimine ylides with a bifunctional catalyst. The ketimine bears an ortho hydroxy group, which increases the acidity of the methylene hydrogen atoms and enhances the reactivity, thus allowing the synthesis of a large variety of α, γ‐diamino acid derivatives with excellent stereoselectivity.